Clinical Effect Analysis of Laparoscopic Nerve-Sparing Radical Hysterectomy in Patients with Early-Stage Cervical Cancer - Hong Xue; Meng Chen; Shuqin Li; Yongchun Zhou (Clinical and Experimental Obstetrics & Gynecology)
Background: There is much controversy about the utility of open and laparoscopic surgery procedures for cervical cancer following the Laparoscopic Approach to Cervical Cancer (LACC) trial. The main objective of this study was to determine the utility of laparoscopic nerve-sparing radical hysterectomy (LNSRH) in improvement of postoperative bladder and rectal function and clinical outcomes of patients with common types of early-stage cervical cancer and tumor diameters <2 cm. Methods: Ninety cases of common types of early-stage cervical cancer with tumor diameters <2 cm were primarily treated with surgery from 2015 to 2021. Forty-five patients underwent LNSRH were classified as the study group and the remaining 45 patients underwent traditional abdominal radical hysterectomy (ARH) and classified as the observation group. The clinical and survival outcomes of the 2 groups were compared. Results: We observed no significant differences in the amount of blood loss, number of lymph nodes dissected, length of vaginal resection and length of parametrium resection between the two groups (p > 0.05). The overall time of operation for LNSRH was longer than that for ARH (p < 0.001). The Visual Analogue Scale (VAS) scores at 8, 24 and 48 hours were significantly different between the two groups (p < 0.001). Catheter retention, flatus and spontaneous defecation times of the LNSRH group were significantly shorter than those of the ARH group (p < 0.05). The proportion of patients with dysuria, abdominal pressure urination and constipation at 6 months after surgery in the LNSRH group was markedly lower relative to the ARH group (p < 0.05). Evaluation of urodynamic parameters 12 months after surgery revealed faster recovery of the LNSRH group (p < 0.05). Postoperative survival rates were not markedly different between the groups (p > 0.05). Conclusions: Laparoscopic nerve-sparing radical hysterectomy is beneficial for patients with common types of early-stage cervical cancer and small tumors. The procedure effectively improves bladder and rectal function after surgery and promotes rapid recovery with no adverse effects on survival outcomes.